1993
DOI: 10.1038/365027a0
|View full text |Cite
|
Sign up to set email alerts
|

Disruption of the CNTF gene results in motor neuron degeneration

Abstract: CNTF is a cytosolic molecule expressed postnatally in myelinating Schwann cells and in a subpopulation of astrocytes. Although CNTF administration prevents lesion-mediated and genetically determined motor neuron degeneration, its physiological function remained elusive. Here it is reported that abolition of CNTF gene expression by homologous recombination results in a progressive atrophy and loss of motor neurons in adult mice, which is functionally reflected by a small but significant reduction in muscle stre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
341
3
4

Year Published

1993
1993
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 548 publications
(357 citation statements)
references
References 34 publications
9
341
3
4
Order By: Relevance
“…To address this issue, we used gene-targeting techniques to produce transgenic mice in which the CNTF gene was disrupted (60). As expected, CNTF null mutants obtained by gene targeting resulting in a complete absence of CNTF protein and corresponding biological activity did not show a reduction of the number of motoneurons during embryonic development (60).…”
Section: Thoenen Hughes and Sendtnermentioning
confidence: 90%
See 2 more Smart Citations
“…To address this issue, we used gene-targeting techniques to produce transgenic mice in which the CNTF gene was disrupted (60). As expected, CNTF null mutants obtained by gene targeting resulting in a complete absence of CNTF protein and corresponding biological activity did not show a reduction of the number of motoneurons during embryonic development (60).…”
Section: Thoenen Hughes and Sendtnermentioning
confidence: 90%
“…However, morphometric analysis of spinal motoneurons demonstrated a gradually increasing atrophy and degeneration of motoneurons accompanied by reactive gliosis, starting at the eighth postnatal week. By 28 weeks, a 22% reduction of the number of motoneurons in the facial nucleus was detectable (60). Although the motor func-tion from plain inspection did not indicate clear-cut signs of motoneuron impairment, measurement of grip strength as a parameter for motor function revealed a small but statistically significant reduction in 28-weekold CNTF null mutants (60) .…”
Section: Thoenen Hughes and Sendtnermentioning
confidence: 99%
See 1 more Smart Citation
“…BainsCat#012704 cfos ‐Cre ERT2 mouseJAX LabsCat#021882 ROSA26‐stop‐ZsGreen1 f / f mouse ( Ai6 )JAX LabsCat#007906 Scgn − /− miceMMRRC for authorsMalenczyk et al (2017) Cntf − / − mice A. GiordanoMasu et al (1993) Scgn‐ Cre mouseG. SzabóDeveloped for this studyAAV8‐EF1a‐double floxed‐hChR2(H134R)‐mCherry‐WPRE‐HGHpAAddgene Viral ServiceCat#20297AAV8‐hSyn‐DIO‐hM3D(Gq)‐mCherryAddgene Viral ServiceCat#44361AAV8‐hSyn‐DIO‐hM4D(Gi)‐mCherryAddgene Viral ServiceCat#44362AAV8‐hSyn‐DIO‐hM3D(Gq)‐mCherryAddgene Viral ServiceCat#44361pAAV‐hSyn‐DIO‐mCherryAddgene Viral ServiceCat#50459AAV‐hSyn1‐GCaMP6f‐P2A‐nls‐dTomatoAddgene Viral ServiceCat#51085 Sequence‐based reagents Primers for CNTFIDTRef#72797892‐3Control siRNASanta CruzCat#sc‐37007SCGN siRNASanta CruzCat#sc‐153255Accell SMARTpool CNTF siRNAGE DharmaconCat#A‐091086Accell SMARTpool SCGN siRNA…”
Section: Methodsmentioning
confidence: 99%
“…The gp130 cytokine family is characterized by functional redundancy, and the phenotypes of mice lacking individual cytokines [12,17,28,29,45] are much less severe than the phenotypes of mice lacking their shared receptors [10,30,46]. Nonetheless, the early and robust expression of CT-1 in the developing heart tube, and the sustained expression of CT-1 in the adult heart, suggested that CT-1 played a unique role in promoting cardiac myocyte survival and hypertrophy during development and after injury.…”
Section: Discussionmentioning
confidence: 99%